Ly49A Transgenic Mice Provide Evidence for a Major Histocompatibility Complex–dependent Education Process in Natural Killer Cell Development - Held, Werner (The Rockefeller University Press, 1997)
The Ly49 natural killer (NK) cell receptors are class I MHC–specific inhibitory receptors that are distributed to overlapping NK cell subsets. The formation of the Ly49 receptor repertoire was examined with transgenic mice that express Ly49A in all NK cells. In MHC class I–deficient mice, the Ly49A transgene did not prevent expression of endogenous Ly49 genes. However, in H-2(d) mice that express a Ly49A ligand, the transgene caused clear alterations in the endogenous Ly49 repertoire. The frequency of NK cells expressing another H-2(d)–specific receptor, Ly49G2(+), was substantially reduced. Reduced numbers of cells expressing endogenous Ly49A was suggested by reduced endogenous Ly49A mRNA levels. These results support the existence of an MHC-dependent education process that limits the number of NK cells that coexpress multiple self-specific Ly49 receptors. Ligand-dependent downregulation of Ly49 cell surface levels was also examined. Cell-surface downregulation occurred even when the transgene was expressed at low levels. The results demonstrate that downregulation of Ly49A cell surface levels is a posttranscriptional event, and argue against a model in which Ly49 receptors are calibrated to specific cell surface levels depending on the available class I ligands.